Studying the Parameters of EDM Based Micro- Cutting Holes Using ANOVA - Shukry H. Aghdeab; Laith A. Mohammed (Engineering and Technology Journal, 2013)
Micro -EDM is one of an important method in machining holes which is used in wide applications to fabricate medical devices and small dies. This work study the process of producing micro holes for copper alloy workpieces using, stainless steel electrode and dielectric solution (tap water), using DC current and low voltage (70V) to cut (0.7mm) thickness of copper (Cu) alloy workpieces in order to obtain the micro holes. This work included an experimental work for electrical discharge machining (EDM) to produce micro holes with different diameters (400, 300, 210, 200, 120, 100, 85, 75, 70) μm. The objective of this work is to obtain an optimal setting of EDM parameters to produce micro holes in copper alloy to achieve the optimal values of required holes diameters. A regression model has been developed to represent this process. An approach has been made to optimize the process parameters (current, gap distance, machining time) using ANOVA analysis. This analysis was performed to obtain the most significant factors influencing the production of micro holes.